Condomínio de lotes: natureza jurídica, fundamentos, modalidades e tutela jurisdicional - Silva, Aurélio Joaquim da (2022)
Condominium of Lots: legal nature, foundations, modalities and judicial protection is based on the social function of the institute under study, which attracts relations of subordination and coordination of the Brazilian legal system, especially between the Constitution of the Republic, the Civil Code and the urban legislation, environmental, administrative, of registry, fiscal and consumer, as well as the microsystem of the collective process. Land subdivision is the division of a plot into lots. These lots, if organized under community life, regulated by a legal transaction of a normative nature called a convention, they will constitute a Condominium of Lots. In its various meanings and designations, in its long historical, jurisprudential and doctrinal construction, Condominium of Lots had always been understood as a special subdivision of land, as opposed to conventional, common, ordinary or open land subdivision, regulated by Federal Law nº 6.766/1979. Provisional Measure No. 759/2016, converted into Law nº 13,465/2017, which provided for rural and urban land regularization, began to provide, on the one hand, the institute of the Condominium of Lots: - in Book III (Real Law) of the Title III (Ownership) of Chapter VII (Building Condominium) in Section IV (Condominium of Lots) of Civil Code/2002, art. 1358-A; and, - in 7th paragraph of 2nd article of Federal Law No. 6,766/1979. On the other hand, the Closed or Controlled Access Subdivision, in 8th paragraph or 2nd article of the same Federal Law No. 6,766/1979. The present work concludes that Condominium of Lots, in spite of being inserted in the chapter of Civil Code/2002 that deals with building condominium, it has the legal nature of being a special subdivision of the land organized in a peculiar condominium form and it is classified under the modalities or species of Closed Block or Closed Allotment, which have their own legal regimes, with similarities, distinctions and different reflexes in tax, administrative, urban and civil law. The investigation was carried out in an interdisciplinary way by the doctrine of civil, urban, environmental, procedural, diffuse and collective rights, registry, notary, administrative and fiscal, whose methodology was guided by the abstract hermeneutic, analytical and pragmatic dogmatics with the objective of highlighting and achieve its legal nature, concept, foundations, definition of its modalities and collective protection of the Condominium of Lots, in order to contribute to effectivity of the social function of the city and adequate implementation of the researched institute, as well as to avoid damage to consumer rights and the urban and environment order of Brazilian municipalities